Nanomaterials-based vaccines to target intracellular bacterial pathogens - Files, Megan A.; Kristjansson, Kadin M.; Rudra, Jai S.; Endsley, Janice J. (Frontiers in Microbiology, 2022)
Development of novel immunization approaches to combat a growing list of emerging and ancient infectious agents is a global health priority. Intensive efforts over the last several decades have identified alternative approaches to improve upon traditional vaccines that are based on live, attenuated agents, or formulations of inactivated agents with adjuvants. Rapid advances in RNA-based and other delivery systems for immunization have recently revolutionized the potential to protect populations from viral pathogens, such as SARS-CoV-2. Similar efforts to combat bacterial pathogens, especially species with an intracellular niche, have lagged significantly. In the past decade, advances in nanotechnology have yielded a variety of new antigen/adjuvant carrier systems for use in vaccine development against infectious viruses and bacteria. The tunable properties of nanomaterial-based vaccines allow for balancing immunogenicity and safety which is a key hurdle in traditional antigen and adjuvant formulations. In this review, we discuss several novel nanoparticle-based vaccine platforms that show promise for use against intracellular bacteria as demonstrated by the feasibility of construction, enhanced antigen presentation, induction of cell mediated and humoral immune responses, and improved survival outcomes in in vivo models.